Gliding motility protein LIMP promotes optimal mosquito midgut traversal and infection by Plasmodium berghei - Egarter, Saskia; Santos, Jorge M.; Kehrer, Jessica; Sattler, Julia M.; Frischknecht, Friedrich; Mair, Gunnar R. (Molecular and biochemical parasitology, 2021)
Substrate-dependent gliding motility is key to malaria transmission. It mediates host cell traversal, invasion and infection by Plasmodium and related apicomplexan parasites. The 110 amino acid-long cell surface protein LIMP is essential for P. berghei sporozoites where it is required for the invasion of the mosquito’s salivary glands and the liver cells of the rodent host. Here we define an additional role for LIMP during mosquito invasion by the ookinete. limp mRNA is provided as a translationally repressed mRNP (messenger ribonucleoprotein) by the female gametocyte and the protein translated in the ookinete. Parasites depleted of limp (Δlimp) develop ookinetes with apparent normal morphology and no defect during in vitro gliding motility, and yet display a pronounced reduction in oocyst numbers; compared to wildtype 82 % more Δlimp ookinetes remain within the mosquito blood meal explaining the decrease in oocysts. As in the sporozoite, LIMP exerts a profound role on ookinete infection of the mosquito.